Assissting Children With Special Educational Needs: Content Analyses - Aleksanyan, Mery
The fluctuations in the mental health of children and adolescents were recording the attention of various experts, related to solving different social problems. For the same reason, there are descriptions of these fluctuations and their classifications (educational, clinical-pedagogical, psychoanalytic, psychoanalytic-pedagogical) in scientific literature. It is estimated that each descriptive explanation of children's fluctuations includes multiple indications or signals of observed fluctuations, without presenting only one profile from the classifications presented in the study. In the phase of improving healthcare, psychology, and childcare, there is a strong need to accurately describe the physical, psycho-physiological, and psychological descriptions of children in order to effectively address their educational and socio-emotional needs. Content analyses is used to understand the clear statement of the situation from different perspectives.
Keywords: Education; Psychology